LB1.3 The impact of hpv vaccination on genital warts in aboriginal australians: analysis of national data. (13th September 2015) - Ali, H; O'Connor, CC; Callander, D; Saulo, D; Graham, S; Kong, M; Regan, DJ; Grulich, AE; Fairley, CK; Guy, RJ; Donovan, B
Abstract : Introduction: Australia funded a national human papillomavirus (HPV) program for girls and young women (12–26 years) from 2007 and for young boys (12–15 years) from 2013. We evaluated the impact of the program in Aboriginal and Torres Strait Islander (Aboriginal) people who suffer disproportionately from HPV-related cancers. Methods: Routinely collected clinical data from 19 sexual health services in four jurisdictions were included. We calculated the proportion of Aboriginal attendees diagnosed with genital warts at first visit, before and after the start of the program, and compared this with non-Indigenous attendees. We calculated percentage change between time periods along with 95% confidence intervals (CI). Final, clean and corrected datasets were received from the participating services in second quarter of 2015; after which the datasets were cleaned and data errors corrected in collaboration with the clinics before data could be analysed in July. Results: From 2004–2014, 215, 599 Australian born attendees were seen; of whom 7.2% identified as Aboriginal. The proportion of Aboriginal women aged <21 years diagnosed with warts decreased by 96.1% (95% CI: 70.8%–99.5%) in the vaccination period, from 7.8% in 2007 to 0.3% in 2014, comparable to the 90.8% (95% CI: 85.5%–94.1%) decline in non-Indigenous women of the same age. The proportion of Aboriginal women aged 21–30 years diagnosed with warts decreased by 75.0% (95% CI: 24.4%–91.9%), from 6.0% to 1.5%; comparable to the 75.4% (95% CI: 68.9%–80.7%) decline in non-Indigenous women. The proportion of Aboriginal heterosexual men aged <21 years diagnosed with warts decreased from 7.3% in 2007 to no diagnosis in 2014 and among Aboriginal heterosexual men aged 21–30 years wart diagnoses decreased by 75.8% (95% CI: 33.6%–91.3%), comparable to the decreases in <21 year old (88.7%; 95% CI: 79.5%–93.8%) and 21–30 year old (68.8%; 95% CI: 63.4%–73.5%) non-Indigenous men. Conclusions: Using genital warts as a proxy measure of the impact of the HPV vaccination program, Aboriginal and non-Indigenous Australians appear to have benefited equally.